Analisis mikrobiologis jajanan makanan di Kantin Pujasera Universitas Pattimura Ambon - Eka Astuty; Andi Wahyuli; Farah Christina Noya (Poltekkes Kemenkes Aceh, 2025)
Background: Snack food is typically prepared and served in open spaces, such as in food courts or by the roadside, which makes it highly susceptible to bacterial contamination. If consumed in certain amounts, these bacteria can cause foodborne illnesses (foodborne diseases).Objective: This study aims to assess the quality of food sold at the Pujasera Canteen of Pattimura University, Ambon, based on microbiological parameters by calculating the Total Plate Count (TPC).Method: This research is a descriptive quantitative study with an observational approach. The samples used consisted of five types of snack foods: noodle with meatballs, egg noodles, chicken rice, fried tubers, and fried rice, which were randomly sampled from sales stands. The study was conducted in May 2024 at the Microbiology Laboratory of the Faculty of Medicine, Pattimura University. Statistical analysis was carried out by calculating the total colonies using the formula TPC (Total Plate Count).Results: The results showed the TPC values for sample A at 1 × 10^6 colonies/g, sample B at 2,5 × 10^7 colonies/g, sample C at 1,2 × 10^7 colonies/g, sample D at 7,3 × 10^7 colonies/g, and sample E at 4,6 × 10^4 colonies/g. Based on these values, four out of the five samples did not meet the criteria set by BPOM (Indonesia’s National Agency of Drug and Food Control), referring to SNI 7388:2009, as they exceeded the maximum microbial contamination limit of <1 × 10^5 colonies/g. Only one sample met the criteria.Conclusion: Four out of the five samples were categorized as having poor quality, as the microbial count exceeded the maximum contamination limit set by SNI.